Proposing an Absorptive Capacity Framework of Small and Medium Sized Enterprises (SMEs) in Construction Industry - Aina Mardia Sallehuddin, Roshartini Omar; Norliana Sarpin (International Journal of Sustainable Construction Engineering and Technology, 2022)
The demand of construction project is increasing from years to years. Therefore, to survive and growth well in the industry, technology and innovation need to be executed by the organisation as both aspects are known as a weapon which helps in enhancing competitive advantage. Consequently, organisation should have the awareness on absorptive capacity to allow such practice is possible. Absorptive capacity is known as a critical item within organisation in order to sustain, grow and compete in the market. In previous research, absorptive capacity had been used to analysis performance at different levels including individual, organisation, industry and country. However, many researchers focus only on large organisation rather than small organisation. Meanwhile, on the different dimension, many researchers outlined the current aspects in measuring absorptive capacity is focus on R&D orientation which is not suitable for small and medium sized enterprises (SMEs) construction organisation. Hence, this paper aims to identify suitable measurement in measuring absorptive capacity level among SMEs within construction industry. Based on the absorptive capacity measurement models synthesis, the researcher found that most of previous research used performance, employee abilities and organisation factors to measure absorptive capacity in the construction industry. This research also considered non R&D absorptive capacity measurement in manufacture sector due to limited reliable literature review in measuring absorptive capacity through its dimensions; acquisition, assimilation, transformation and exploitation. A proposed framework that represents absorptive capacity measurement among SMEs is established at the end this paper.